Teknologi Pengelolaan Tumpangsari Jagung-Padi dan Jagung-Kedelai di Lahan Kering - Suwardi, M. Aqil; Nining Nurini Andayani; Fahdiana Tabri (Universitas Muhammadiyah Purworejo, 2022)
Rice, corn and soybeans are plants as a source of food and feed in Indonesia. Consumption of food crops (rice, corn and soybeans) has increased every year along with the population and livestock. One alternative to meet the needs of staple food and feed is the corn-rice and corn-soybean intercropping system. The aim of the study was to verify the corn-rice and corn-soybean intercropping model for optimizing production and knowing the spacing of corn, rice, soybeans on the same land and season and the comparison of the number of rows of corn in the intercropping of corn-rice, corn and soybeans with optimal corn production. Intercropping is a cropping system by planting more than one type of plant/commodity at the same time or at a certain time in one growing season. The research was carried out in KP. Bajeng Gowa from August to November 2019. The study used a factorial randomized block design with 3 (three) replications. The first factor is 1) the first planting distance of corn-rice-soybean is (maize (160 x 40) x 20 cm (3 rows of plants), upland rice 20 cm x 20 cm (5 seeds/hole, 4 rows of plants), soybean 40 cm x 20 cm (2 seeds/hole 3 rows of plants) and the distance of corn from rice and soybeans is 40 cm, 2) the second planting distance of corn-rice-soybean (Dena 1) is corn (160 x 40) x 20 cm ( 1 seed/hole, 4 rows of plants), upland rice 20 cm x 20 cm (5 seeds/hole, 4 rows of plants), soybean 40 cm x 20 cm (2 seeds/hole, 3 rows of plants) and distance of corn from rice and soybeans 40 cm. The second factor is the corn varieties, namely Nasa-29, JH 45, JH 27, and Bisi 18. For rice and soybeans, plant them at the same time as 10-15 before planting corn. The results showed that the productivity of maize (6.92-8.46 t/ha) intercropped with soybeans was higher than maize (5.12-5.24 t/ha) intercropped with rice at a spacing of maize (120-40) x 20 cm (3 rows of maize) and maize productivity (7.05 – 8.59 t/ha) intercropped with rice were higher than maize (6.43-7.72 t/ha) intercropped with soybeans at a spacing of maize (120-40 ) x 20 cm (3 rows of corn).